MENJADIKAN EKARISTI SEBAGAI PUNCAK DAN SUMBER KEHIDUPAN GEREJA - Madya Utama, Ignatius Loyola (P3TK, Sanata Dharma University, 2014)
Members of the Catholic Church believe the Churchs teaching on Eucharistic celebration as the summit and the fount of the Churchs life. They even believe that the Eucharist is the summit and the fount of their faith lives. Unfortunately, the real meaning of this belief oftentimes is not well understood. As a result, the Eucharistic celebration does not really influence their way of thinking and their way of lives. This article tries to discover and present such meaning, with the hope that by having such understanding all members of the Catholic Churchincluding religious and priestswill make it as their way of thinking and living. The Eucharistic celebration will become the summit of the Churchs life if those who celebrate it have already tried to build a communion before the celebration takes place. It will become the fount of the Churchs life if those who celebrate it will try their best to become a Eucharistic people by becoming promotors of peace and solidarity.